Effectiveness of a 6-Month 22.5-mg Leuprolide Acetate Depot Formulation With Tamoxifen for Postoperative Premenopausal Estrogen Suppression in Hormone Receptor-Positive Breast Cancer - Wu, Zhen-Yu; Lee, Young-jin; Kim, Heejeong; Lee, Jongwon; Chung, Il Yong; Kim, Jisun; Lee, Saebyeol; Son, Byung-Ho; Kim, Sung-Bae; Jeong, Jae Ho; Gong, Gyungyub; Ahn, Sei-Hyun; et al. (Frontiers in Oncology, 2021)
Background: In patients with hormone receptor-positive (HR+)/premenopausal breast cancer, luteinizing hormone-releasing hormone analogs (LHRHas) are used as standard endocrine treatment. Based on previous clinical studies, 1-month formulations are recommended in most breast cancer treatment guidelines, but long-acting formulations facilitate reductions in side effects and patient discomfort caused by frequent administration. However, few efficacy studies have been conducted on 6-month formulations. Therefore, this study aimed to evaluate the efficacy of 6-month formulations of LHRHas. Methods: This retrospective study was conducted from January 2018 to December 2019 and involved premenopausal patients with HR+ breast cancer administered 6-month LHRHas as adjuvant treatment after surgery, and those previously administered chemotherapy or other LHRHa types were excluded. Patients’ estradiol (E2) and follicle-stimulating hormone (FSH) levels were measured before surgery, and their E2 levels were also measured at 3, 6, 12, 18, and 24 months at periodic postsurgical examinations. Results: A total of 228 patients were included, and the median patient age was 44 (range, 25–54) years. The mean serum E2 and FSH levels before surgery were 69.7 (range, 4–683) pg/mL and 7.3 (range, 0.4–88.9) mIU/mL, respectively, whereas the mean serum E2 level monitored at intervals during the 6-month LHRHa administration was 5.5 (range, 4.0–52) pg/mL. No women menstruated during the follow-up period after the LHRHas administration, and the E2 levels were less than 30 pg/mL in all patients except one. Conclusions: The 6-month LHRHa formulation adequately suppressed ovarian function in premenopausal patients with HR+ breast cancer. This indicates that long-acting LHRHas can be effectively used for patient convenience and that there is high compliance with long-term use.